2018
DOI: 10.1080/02640414.2018.1535772
|View full text |Cite
|
Sign up to set email alerts
|

Road cycle TT performance: Relationship to the power-duration model and association with FTP

Abstract: To determine the accuracy of critical power (CP) and Wʹ (the curvature constant of the power-duration relationship) derived from self-paced time-trial (TT) prediction trials using mobile power meters to predict 16.1-km road cycling TT performance. This study also aimed to test the agreement between functional threshold power (FTP) and CP. Methods: Twelve competitive male cyclists completed an incremental test to exhaustion, a 16.1-km road TT, an FTP test, and 4-5 self-paced TT bouts on a stationary bike within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 38 publications
(59 reference statements)
3
47
0
Order By: Relevance
“…While the present study adopted MLSS as the criterion measure for the upper limit of metabolic stability and compared this with the FTP95%, other studies have investigated the correspondence between FTP tests and different markers of critical intensity. For example, Morgan et al 9 , found a close relationship between CP (275 ± 42W) and FTP95% (278 ± 42W). However, similar to our results, they found that the corresponding limits of agreement (+10.9% to 13.1%) exceeded those that would allow the two measures to be used interchangeably with a high level of confidence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While the present study adopted MLSS as the criterion measure for the upper limit of metabolic stability and compared this with the FTP95%, other studies have investigated the correspondence between FTP tests and different markers of critical intensity. For example, Morgan et al 9 , found a close relationship between CP (275 ± 42W) and FTP95% (278 ± 42W). However, similar to our results, they found that the corresponding limits of agreement (+10.9% to 13.1%) exceeded those that would allow the two measures to be used interchangeably with a high level of confidence.…”
Section: Discussionmentioning
confidence: 97%
“…This is pertinent as many regard MLSS to be the criterion measure for tolerable exercise 2 . Furthermore, although cross-sectional comparisons between FTP95% and other markers of performance have been made [5][6][7]9 , no study has evaluated the ability or sensitivity of the FTP95% test to track changes in fitness level on a longitudinal basis.…”
Section: Introductionmentioning
confidence: 99%
“…adopted the "even" [17] or "parabolic-shaped" [12,13] pacing strategy. Therefore, we believe that the pacing strategy for the 20min TT was modulated by the long warm-up and by the [La] before the start of the TT (4.9 ± 2.6 and 4.8 ± 2.5 mmol L − 1 ; test-retest, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, Borszcz et al [7,8] and Valenzuela et al [10] are the only studies that have used the warm-up recommended by the authors [6]. Others have not used this section of the protocol [11][12][13]. Borszcz et al [7] reported high blood lactate concentrations ([La]) before the start of the test (6.5 ± 2.9 mmol • L − 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation